Detection of Pipeline Deformation Induced by Frost Heave Using OFDR Technology - Jiang, Tao; Zhu, Jing-wen; Shi, Yi (Frontiers in Physics, 2021)
Oil and gas pipelines are critical structures. For pipeline in seasonal frozen soil area, frost heave of the ground will result in deformation to the pipeline. If the deformation continually increases, it will seriously threaten the pipeline safety. Therefore, it is important to monitor the deformation of the pipeline in frozen soil area. Since optic frequency domain reflectometer (OFDR) technology has many advantages in distributed strain measurement, this paper utilized the OFDR technology to measure the distributed strain and use the plane curve reconstruction algorithm to calculate the deformed pipeline shape. To verify the feasibility of this approach, a test was conducted to simulate the pipeline deformation induced by frost heave. Test results showed that the pipeline shape can be reconstructed well via the combination of OFDR and curve reconstruction algorithm, providing a valuable approach for pipeline deformation monitoring.